The Effectiveness of Start with Simple Stories (SSS) Method on EFL Students’ Vocabulary Attainment - Istithoah, Dinies Hanif; Sholikhah, Masriatus (Journal of Management, Education and Communication, 2025)
This study investigates the effectiveness of the Start with Simple Stories (SSS) method in enhancing vocabulary attainment among English as a Foreign Language (EFL) students. The research was conducted at SMP Plus Al-Islamiyah VII Al Batani in Tangerang Selatan, using a quasi-experimental design involving two groups of eighth-grade students. The experimental group received vocabulary instruction through the SSS method, while the control group was taught using conventional techniques. Pre-test and post-test vocabulary assessments were administered to both groups. Statistical analysis, including ANCOVA, was employed to determine the significance of the treatment effect. The findings revealed that the SSS method had a significant positive effect on students’ vocabulary mastery, highlighting the potential of extensive reading-based strategies in EFL classrooms.